1988
DOI: 10.1016/0014-5793(88)81378-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the β2‐adrenergic receptor and its mRNA in the rat ventral prostate by testosterone

Abstract: To investigate the regulation of fl2AR expression in rat ventral prostate the effects of castration and testosterone replacement on the fl2AR were studied by ligand binding and Northern blot analysis. Orchidectomy depressed fl2AR number by 50% within 4 days and testosterone administration to 4-day castrates produced a rapid and complete recovery offl2AR number within 24 h. In contrast to receptor number, fl2AR mRNA levels did not change relative to total RNA following castration. However, during the testostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…mRNA transcription rate was noted after only 20 -30 min of treatment. Such a rapid change in mRNA transcription is mostly transient (Noguchi et al, 1982;Collins et al, 1988). In our acute experiments, we also found that changes in mRNA levels were small (15-25%) and transient (data not shown).…”
Section: Effect Of a Single Administration Of Cocaine On Binding And supporting
confidence: 67%
“…mRNA transcription rate was noted after only 20 -30 min of treatment. Such a rapid change in mRNA transcription is mostly transient (Noguchi et al, 1982;Collins et al, 1988). In our acute experiments, we also found that changes in mRNA levels were small (15-25%) and transient (data not shown).…”
Section: Effect Of a Single Administration Of Cocaine On Binding And supporting
confidence: 67%
“…In comparing the regulation of epididymal Sa-reductase enzyme activity and the expression of its mRNAs, it is apparent that another potential regulatory site for the enzyme is at the level of the protein itself. It is interesting to note that post-transcriptional regulation has also been proposed for several other epididymal proteins (Cornwall and Hann, 199Sb;Brooks et al, 1986;Cyr et al, 1993;Ghyselinck et al, 1990) and other proteins in the male reproductive tract (Kistler et al, 1981;Collins et al, 1988).…”
Section: Regulation Of Epididymal Sa-reductasesmentioning
confidence: 96%
“…The small but signi®cant reduction in b 2 -AR mRNA in RU-486-treated ob/ob supports this suggestion in part. Since the b 2 -AR is also positively regulated by testosterone, 50 the poor pituitary support for testicular function in ob/ob mice 34 may be counteracting the stimulatory effects of glucocorticoids on b 2 -AR expression. The effect of RU-486 on testosterone levels was not evaluated in the present study, but as with thyroid hormones, it seems unlikely that the antagonist would signi®cantly alter testicular function.…”
Section: Ru-486 Ameliorates Diabetesmentioning
confidence: 99%